Trajectories of Emerging Adults’ Binge Drinking and Depressive Symptoms and Associations With Sexual Violence Victimization: Examining Differences by Sexual and Gender Minority Status - Siconolfi, Daniel (Journal of interpersonal violence, 2023)
We examined longitudinal associations between binge drinking (BD), depressive symptoms, and sexual violence (sexual harassment and sexual assault) among sexual and gender minority (SGM) and non-SGM emerging adults. Data were drawn from four annual web-based surveys of a diverse cohort of 2,553 emerging adults, spanning from approximately age 19 (2016) to age 22 (2020). About 18% were SGM individuals. We tested a multigroup parallel process latent growth curve model (recent depression symptoms; past-year BD) with time-varying covariates (past-year sexual harassment; sexual assault) to determine associations of sexual violence with BD and depression outcomes over time, and whether growth curves and associations differed by SGM status. For both SGM and non-SGM emerging adults, past-year sexual harassment was associated with depressive symptoms at each time point, but harassment was not associated with BD. For both groups, sexual assault was associated with both depressive symptoms and BD. To our knowledge, this is the first study to examine longitudinal, contemporaneous associations of sexual violence (including both harassment and assault as distinct constructs), with BD and depressive symptoms among racially and ethnically diverse emerging adults, comparing SGM and non-SGM groups. Although our models do not disentangle directionality or causality, the findings suggest the need to address sexual violence victimization (assault and harassment) in the context of depression screening and treatment, and vice versa. We discuss a number of intervention strategies currently in use for an implicitly non-SGM general population that could be adapted for greater inclusion of and relevance to SGM populations.